Kesadaran Lingkungan Siswa Sekolah Adiwiyata - Yanti Dasrita; Zulfan Saam; Bintal Amin; Yusni Ikhwan Siregar (Dinamika Lingkungan Indonesia, 2015)
Environmental education enrole strategically in changing human perception andattitude on the environmental problem in the long run. The current study attempt to analyzeenvironment awareness among the high school students in the village, small city and big cityand that factors affecting the awareness. Apparently, knowledge, attitude and behaviourpartially do not influenced environmental awareness of the student in the school obtainingadiwinata and with that non-adiwinata. However, simultantly, student attitude had an effectto student awareness of adiwiyata school, while in non adiwinata school both attitude andbehaviour influenced student awareness.